Gnomon : a novel - Harkaway, Nick, 1972- (Alfred A. Knopf, 2018)
"From the widely acclaimed author of The Gone-Away World and Tigerman, a virtuosic new novel and his most ambitious book yet--equal parts dark comedy, gripping detective story, and mind-bending philosophical puzzle--set in a not-too-distant-future, high-tech surveillance state. In the world of Gnomon, citizens are ceaselessly observed and democracy has reached a pinnacle of "transparency." When suspected dissident Diana Hunter dies in government custody during a routine interrogation, Mielikki Neith, a trusted state inspector, is assigned to the case. Immersing herself in neural recordings of the interrogation, she finds a panorama of characters and events that Hunter gave life to in order to forestall the investigation: a lovelorn financier in Athens who has a mystical experience with a shark; a brilliant alchemist in ancient Carthage confronting the unexpected outcome of her invention; an expat Ethiopian painter in London designing a controversial new video game. In the static between these mysterious visions, Neith begins to catch glimpses of the real Diana Hunter--and, alarmingly, of herself, the staggering consequences of which will reverberate throughout the world. Gnomon is a dazzling, panoramic achievement from one of the most original voices in contemporary fiction"--